2014
DOI: 10.1155/2014/834629
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of High Surface Area Mesoporous Silica Powder Using Anionic Surfactant

Abstract: Over the past several years, synthesized mesoporous nanosilica (SiO 2 ) powders have been developed by many different methods. The methods include precipitation and microemulsion, the Stöber method, chemistry, and technology. In this study, mesoporous silica powders are synthesized by the sol-gel method. The sol-gel method obtains a high purity silica powder; however, the process yields a low percentage. Past syntheses of SiO 2 powder precursors are expensive, but this study needs to find a replacement precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…Then, it has high surface area that forms anion surfactants, which is used in many industrial applications [19]. Also, the crystalline-SiO 2 [1] is recorded in Figure 4 Thus, it's found that the sonication time is controlled in the form and size of powder produced. Due to the ultra-sonication process is a growth inhibition technique especially in presence of alkali chemical etching process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, it has high surface area that forms anion surfactants, which is used in many industrial applications [19]. Also, the crystalline-SiO 2 [1] is recorded in Figure 4 Thus, it's found that the sonication time is controlled in the form and size of powder produced. Due to the ultra-sonication process is a growth inhibition technique especially in presence of alkali chemical etching process.…”
Section: Resultsmentioning
confidence: 99%
“…The silica (SiO 2 ) powder is noted as competent materials because of their unique characteristics (low density, high surface area and high specific strength) [1] [2] [3]. SiO 2 is a very interesting material for using in many fields [4] [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drawbacks associated with the use of NMs for conventional or disposable electrode modification process include time consuming multiple steps in modification techniques such as electrodeposition [13,16] and sol-gel processes [22,23], the requirement of polishing the electrode surface before modification [13,14,24], the use of reagents to enhance the porosity of the electrode surface [25], the requirement of technical skills for modification [13,16,22,23], and the limited stability of the modified electrode surface, usually 5-7 days [26,27]. Most recent reports on the preparation and/or modification of electrodes with NMs have drawbacks such as use of large quantities of NMs (e.g.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…[1][2][3][4][5][6] 이러한 나노실리카 분말의 제조 방법으로는 광물 의 분쇄, 염화실리카를 이용한 기상반응 7) , TEOS(Tetraethylorthosilicate)나 물유리(sodium silicate)를 이용한 졸 -겔(Sol-Gel) 공정이 있다. …”
Section: 서 론unclassified